New pricing theory of intelligent flexible transportation - Andrejszki, Tamás; Török, Árpád (Transport, 2018)
In the paper, possible pricing structures of flexible transport systems have been investigated. After a brief introduction into demand responsive systems, the currently used pricing systems have been analysed. Having reviewed the conventional pricing methodologies – in line with the average cost and marginal cost based methods – the advantages and the disadvantages of particular systems are presented. What is more, that traditional pricing theory enabled to order costs of flexible transportation systems only approximately to passengers in proportion to their demanded transportation performance, thus traditional pricing framework is not able to fully meet the principle of fairness. For reaching the highest level of fairness loops a fictive unit of individual trips is introduced as the base of pricing. When applying individual loops is gives a unique approach to describe unit cost of the operators especially considering that empty runs are taken into account in a fair way. Beside fairness, it is also an essential objective to represent economies of scale and the preference of early bookings in the pricing methodology. Accordingly, the below presented ‘mixed price system’ had good results in the reduction of average fares related to new travellers and also in the improvement of attraction related to ‘early birds’. Therefore, the goal of this research was to define the direction and the aspects of the development process related to the pricing methods of flexible transportation.First published online 13 July 2015